SOLAR POWERED AUTOMATIC SOUND MAKER FOR MILLET CROPS - B.SURRESH RAM, P.MAHESH BABU, G.KARTHIK REDDY,K.VARSHINI, V.THARUNI, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The main problem of today’s agriculture is the increasing labor cost, so our idea helps to reduce that labor cost especially focusing on millet crops because all the farmers are cultivating paddy and due to that the supply of paddy is triple than the actual demand of our state. So, if some of the farmers change to millet crops by our device, they get good profits as thus device decreases the labor cost and the millet crops are sold at moderately high price than the paddy. The cost of the device can be reduced if it is produced in bulk. As this is a pure mechanical device the farmers can easily maintain and service the device themselves.Our device runs on solar power which is abundant in the season when millet crops are grown because millet are hot weather crops, neglecting the initial investment for moderate to big farmers this device would push them into profits from their first harvest of crops.